COVID-19 vaccination for pregnant women: strategies for enhanced coverage - John, Jennifer Britto; Devanbu, Vinoth Gnana Chellaiyan; Kandaswamy, Vijayalakshmi (Indian Journal of Community Health, 2021)
Following the recommendations from the National Technical Advisory Group (NTAG) on Immunization, the Government of India approved three vaccines – an inactivated vaccine, Covaxin and two non-replicating vector-based vaccines, Covishield and Sputnik V for restricted use in an emergency for pregnant women.(1)The late approval of vaccination of pregnant women was due to a lack of evidence, because pregnant women were excluded from previous COVID vaccination trials. The restricted use of this vaccine recommended by NTAG also complies with the regulations of the Centers for Disease Control and Prevention (CDC), the American College of Obstetricians and Gynecologists, and the American Academy of Pediatrics. (2-4)